Effect of Growth Hormone on Uterine Receptivity in Women With Repeated Implantation Failure in an Oocyte Donation Program: A Randomized Controlled Trial - Altmäe, Signe (J Endocr Soc, 2017)
BACKGROUND AND OBJECTIVE: Administration of growth hormone (GH) during ovarian stimulation has been shown to improve success rates of in vitro fertilization. GH beneficial effect on oocyte quality is shown in several studies, but GH effect on uterine receptivity is not clear. To assess it, we studied whether GH administration can improve the chance of pregnancy and birth in women who experienced repeated implantation failure (RIF) using donated oocyte programs. DESIGN AND STUDY POPULATION: A total of 105 infertile women were enrolled in the randomized controlled trial: 70 women were with a history of RIF with donated oocytes, and 35 infertile women underwent the first oocyte donation attempt. Women receiving donated oocytes were treated with progressively increasing doses of oral estradiol, followed by intravaginal progesterone after previous pituitary desensitization with gonadotropin-releasing hormone agonist. Thirty-five RIF patients were treated with GH (GH patients), whereas the rest of the 35 RIF patients (non-GH patients) and 35 first-attempt patients (positive control group) were not. RESULTS: RIF patients receiving GH showed significantly thicker endometrium and higher pregnancy and live birth rates as compared with RIF patients of non-GH study group, although these rates remained somewhat lower as compared with the non-RIF patients of the positive control group. No abnormality was detected in any of the babies born. CONCLUSION: Our data of improved implantation, pregnancy, and live birth rates among infertile RIF patients treated with GH indicate that GH improves uterine receptivity.